Cognitive changes preceding Parkinson's disease: a systematic review and meta-analysis of prospective population-based studies - Peña Arauzo, Noelia; Theyer, Christoph; Krismer, Florian; Djamshidian, Atbin; Poewe, Werner; Horlings, Corinne; Heim, Beatrice; Zamarian, Laura; Mahlknecht, Philipp (Frontiers in Aging Neuroscience, 2025)
IntroductionVarious non-motor symptoms have been studied as part of the prodromal phase of Parkinson's disease (PD). However, studies assessing cognitive changes are scarce.MethodsWe systematically searched PubMed and SCOPUS to identify prospective, population-based studies that reported on cognitive performance in individuals without PD at baseline, the incidence of PD at follow-up, and comparisons of cognitive performance between participants who developed PD and controls.ResultsTwelve studies were identified, including a total of 524,807 participants, of whom 2,939 developed PD. Four studies found differences in global cognition and a meta-analysis showed that individuals who developed PD scored 0.3 points lower than controls on the Mini-Mental State Examination at baseline. Cognitive changes were most frequently observed in tests of executive function, processing-speed and attention, and less frequently in visuospatial/visuoconstructive skills and memory. Due to the heterogeneity of the assessment methods used, it was not possible to conduct further meta-analyses.ConclusionsCognitive changes may be part of the clinical picture in prodromal PD cohorts derived from the general population. Further population-based studies with large samples and long-term follow-up are needed to better understand their extent and significance.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024547252, identifier: CRD42024547252.